Rancang Bangun REFLECTOR Untuk Mengoptimalkan Daya Serap Matahari Pada Panel Surya Dengan Variasi Sudut Guna Menghasilkan Daya Optimal - Hariyanto, Sugeng (Universitas Pendidikan Nasional, 2021)
Various kinds of treatments given to solar panels illustrate efforts to increase the output power of solar panels and the efficiency of solar cells. In the following research, we will analyze the differences in the output power and efficiency of solar cells that have received different treatments. In the solar panel that will be analyzed in this study is the addition of a reflector to solar cells with a reflector tilt angle of 90 ° and 60 ° as a form of variation of radiation amplification. The idea for the use of a reflector is to increase the yield of solar cell input radiation. After testing, the output power produced by solar cells increases as the radiation received by the solar panels increases and the efficiency of the solar panels decreases as the temperature of the solar cells increases.